Determining Leukocyte Origins Using Parabiosis in the PyMT Breast Tumor Model - Franklin, Ruth A. (Bio Protoc, 2015)
Tumors develop in a complex microenvironment alongside numerous cell types that impact their survival. Immune cells make up a large proportion of these accessory cells and many are known to promote tumor progression. Macrophages, in particular, are associated with poor patient prognosis and are therefore potential candidates for therapeutic targeting in cancer. However, to develop successful strategies to target macrophages, it is important to clarify whether these cells are derived from blood-borne precursors or a tissue-resident population. Parabiosis, or the surgical connection of two mice resulting in a shared blood circulation, allows the distinction between these two cellular sources. Here, we describe the use of parabiosis to define cell ontogeny in a mouse model of breast cancer.